PENGGUNAAN MEDIA GAMBAR DALAM PENGAJARAN BAHASA INDONESIA UNTUK MENINGKATKAN KETERAMPILAN MEMBACA DI SEKOLAH DASAR - Fatin Adelya Putri; Sakinah Hasbi, Juliana Nur Azizah Siregar, Muhammad Taufik Hidayat Lubis, Amri, Ahmad Tarmizi Hasibu (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
The purpose of this study is to explore the use of visual media in teaching Indonesian language in elementary schools to enhance students' reading skills. The research method employed is a literature review. This study involves the collection, assessment, and interpretation of information from various relevant sources such as books, journal articles, research reports, and other published materials. The findings indicate that the use of visual media in teaching Indonesian language in elementary schools significantly improves students' reading skills, enhances students' interest in reading materials, makes texts more engaging, and facilitates understanding, particularly for early readers. Visuals help students better grasp the context of texts or stories, build clearer mental images of the content, and improve vocabulary and comprehension of difficult words or phrases. This approach also supports the development of students' visual skills, including those with special needs, creating an inclusive and supportive learning approach for all elementary school students